Characterization of a Dimeric Arginase From Zymomonas mobilis ZM4 - Hwangbo, Seung-A; Kim, Ji-Won; Jung, Sun-Ju; Jin, Kyeong Sik; Lee, Jie-Oh; Kim, Jeong-Sun; Park, Suk-Youl (Frontiers in Microbiology, 2019)
Many organisms have genes to protect themselves from toxic conditions such as high ethanol and/or ammonia concentrations. When a high ethanol condition is induced to Zymomonas mobilis ZM4, a representative ethanologenic organism, this bacterium overexpresses several genes to overcome this ethanol stress. Among them, we characterized a gene product annotated as an arginase (zmARG) from Z. mobilis ZM4. Even though all of the arginase-determining sequence motifs are not strictly conserved in zmARG, this enzyme converts L-arginine to urea and L-ornithine in the presence of a divalent manganese ion. The revealed high-resolution crystal structure of zmARG shows that it has a typical globular / arginase fold with a protruded C-terminal helix. Two zinc ions reside in the active site, where one metal ion is penta-coordinated and the other has six ligands, discerning this zmARG from the reported arginases with two hexa-liganded metal ions. zmARG forms a dimeric structure in solution as well as in the crystalline state. The dimeric assembly of zmARG is formed mainly by interaction formed between the C-terminal -helix of one molecule and the /hydrolase fold of another molecule. The presented findings demonstrate the first dimeric arginase that has two metal ions of different numbers of ligands and is formed by the C-terminal tail.